1999
DOI: 10.1046/j.1525-1438.1999.99057.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment evaluation of adnexal tumors predicting ovarian cancer

Abstract: Kobal B, Rakar S, Ribic-Pucelj M, Tomazevie T, Zaletel-Kragelj L. Pretreatment evaluation of adnexal tumors predicting ovarian cancer. The objective of this study was to determine the ability of tumor marker assessment, gray-scale transvaginal with color Doppler ultrasonography to predict ovarian malignancy. One hundred thirty-four subjects with ovarian masses who entered the study prospectively underwent pelvic examination, tumor marker assessment and gray-scale transvaginal with color flow Doppler ultrasonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…20 Similarly, Kobal B et al reported 31.8% of benign lesions and 62.5% malignant lesions were multilocular. 23 Thus the present study and other studies mentioned above suggest that the malignant lesions are predominantly multilocular. The gray scale morphology in our sample size revealed that 71.4% of the benign tumors were cystic.…”
Section: Gray Scale Ultrasoundsupporting
confidence: 77%
“…20 Similarly, Kobal B et al reported 31.8% of benign lesions and 62.5% malignant lesions were multilocular. 23 Thus the present study and other studies mentioned above suggest that the malignant lesions are predominantly multilocular. The gray scale morphology in our sample size revealed that 71.4% of the benign tumors were cystic.…”
Section: Gray Scale Ultrasoundsupporting
confidence: 77%
“…43.5% cases of malignant tumors had ascites, whereas 5.71% benign tumours of mucinous cystadenomas had ascites. Prior studies have similarly found that papillary projections and ascites are indicative of malignancy [ 16 ]. Others have also noted that 41% cases of stage IV epithelial ovarian cancer have papillary projections [ 17 ].…”
Section: Discussionmentioning
confidence: 99%